2018
DOI: 10.29252/archhygsci.7.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ecological Hazard of Heavy Metals (Cr, Zn, Cu, Pb) in Surface Sediments of The Bashar River, Yasouj, Iran

Abstract: Background & Aims of the Study: Heavy metals pollution in aquatic ecosystems threats living organisms' health and environment. Hence, the present study aims to assess concentration of lead, chromium, copper, zinc and their ecological risk in the surface sediments of the Bashar River during the summer and winter seasons. Materials & Methods: This is a field study; sampling of surface sediment was done in 8 stations in 2016. The samples were digested by the composition of ratio of 1:4 Percholoric acid and Nitric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…In the present study, the observed metal concentration increases in seawater during the rainy season showed a very close similarity with other reported studies such as Radakovitch et al (2008) [38] and Sharma et al (2018) [39]. The lower concentration of HMs during the summer may be due to the dilution effect of the seawater [40,41] where the winter season was longer than the summer season. In addition, the higher concentration of metals during the rainy season might be due to the perturbation of sea bed by the longshore current, upwelling phenomenon, and waves that could increase metals concentration in seawater and sediment [38].…”
Section: Seawater Variationssupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the observed metal concentration increases in seawater during the rainy season showed a very close similarity with other reported studies such as Radakovitch et al (2008) [38] and Sharma et al (2018) [39]. The lower concentration of HMs during the summer may be due to the dilution effect of the seawater [40,41] where the winter season was longer than the summer season. In addition, the higher concentration of metals during the rainy season might be due to the perturbation of sea bed by the longshore current, upwelling phenomenon, and waves that could increase metals concentration in seawater and sediment [38].…”
Section: Seawater Variationssupporting
confidence: 92%
“…The maximum and minimum concentration was observed in spring and winter as 0.44 ± 0.001 and 0.02 ± 0.002 (mg/l), respectively, that is because of entering run-off and transporting sediments containing this metal to the sea (Table 3). Fluctuation in flows to the sea, rainfall, water drainage, and run-off are the most important reasons for changes in the concentration of Cd in seawater [40].…”
Section: Seawater Variationsmentioning
confidence: 99%
“…A considerable contamination (3 ≤ CF < 6) with Cr was detected at the sampling point (S3). This sampling site is located in proximity to tanning industries which release untreated or poorly treated tannery wastewaters usually loaded with Cr (Mortazavi and Hatami 2018;Alemu et al 2016;Xia et al 2018) into the river. Similarly, a considerable sediment contamination (3 ≤ CF < 6) with Pb detected at sampling site (S5) and very high contamination (CF > 6) at sampling sites (S4) and (S6) (Fig.…”
Section: Contamination Factor (Cf)mentioning
confidence: 99%
“…In all sampled sites, the CF values for Cd (CF > 6) found to be in (class 4) exhibiting a very high (CF > 6) level of sediment contamination. Cd can be generated from multiple sources of inputs in downstream; these include electroplating, batteries, paints and pigments factories, garages, vehicles washing, domestic and municipal wastes (Mortazavi and Hatami 2018), agricultural use of phosphorus, zinc and iron fertilizers (Manoj and Padhy 2014).…”
Section: Contamination Factor (Cf)mentioning
confidence: 99%
“…The Bashar River is one of the biggest tributaries of the Tigris-Euphrates basin in Kohkiluyeh and Boyer-Ahmad Province with rich fish diversity, being located in southwest, as the sub-basins of the Karun River, which originates from the Sepidan Mountains in Fars province. It crosses the Pataveh region, joins the Khersan River and finally flows into the Karun River (Jamali et al, 2015;Mortazavi and Hatami, 2018). This river is being exploited for various agricultural, industrial, and recreational activities, thereby greatly contributing to the economy of Yasuj city.…”
Section: Introductionmentioning
confidence: 99%